Analisis Faktor-Faktor yang Mempengaruhi Kepercayaan Muzakki terhadap Lembaga Amil Zakat Berdasarkan Prinsip Islamic Good Corporate Governance - Khalila Husnasari; Ervina Rosarina Hasibuan; Muhammad Iqbal (Dharma Ekonomi, 2025)
The purpose of this study is to use the Theory of Islamic Good Corporate Governance (IGCG) methodology to determine the elements that affect muzakki's faith in paying zakat through zakat institutions. Based on earlier research and literature, this study examines the relationship between the degree of muzakki trust and Islamic values such amanah (accountability), tabligh (transparency), fatanah (competence), and religiosity. Furthermore, additional elements like reputation, contentment, and service quality are examined as significant factors in establishing trust. The findings demonstrate that the majority of earlier research discovered a strong positive correlation between these factors and muzakki trust. Nonetheless, there are conflicting findings on the factors of openness and accountability, which in certain research actually indicate a detrimental impact. This discrepancy highlights the necessity for more study to reevaluate these two factors' roles in the context of zakat management. Theoretically, the adoption of Islamic Good Corporate Governance should boost muzakki involvement in zakat contributions by enhancing accountability, transparency, and public trust in zakat administration organizations.